The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s40615-021-00968-y
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating SARS-CoV-2 Transmission in Hispanic and Latino Communities—Prince William Health District, Virginia, June 2020

Abstract: Objectives To identify factors contributing to disproportionate rates of COVID-19 among Hispanic or Latino persons in Prince William Health District, Virginia, and to identify measures to better engage Hispanic and Latino communities in COVID-19 mitigation. Methods Data collection proceeded via three methods in June 2020: a quantitative survey of Hispanic or Latino residents, key informant interviews with local leaders familiar with this population, and focus group discussions with Hispanic or Latino community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…Immigration concerns also deterred Latino communities from considering being vaccinated/tested. Although this study included urban and rural Latino communities in California mostly from Mexico, similar findings were also reported in the state of Virginia among Latino communities from other heritages [ 26 ]. Latino immigrants’ avoidance of public benefit programs was known before the pandemic [ 28 ], however a study [ 29 ] found that the avoidance of public resources among Latino immigrant families intensified after the 2016 presidential election.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Immigration concerns also deterred Latino communities from considering being vaccinated/tested. Although this study included urban and rural Latino communities in California mostly from Mexico, similar findings were also reported in the state of Virginia among Latino communities from other heritages [ 26 ]. Latino immigrants’ avoidance of public benefit programs was known before the pandemic [ 28 ], however a study [ 29 ] found that the avoidance of public resources among Latino immigrant families intensified after the 2016 presidential election.…”
Section: Discussionsupporting
confidence: 56%
“…The few studies that focused on the impact of COVID-19 on Latino communities consistently found that these communities reported the financial constraints that threaten employment and immigration status especially if they tested positive [ 21 , 24 , 25 ]. Since many Latino individuals work in occupations considered essential and are likely to work in conditions with limited access to proper PPE and limited social distancing [ 26 , 27 ], their risk for COVID-19 further contributes to financial concerns.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 The pandemic has shown that there are not only material barriers to care, but also racial, ethnic, and political difficulties in the uptake of mitigation protocols, associated with factors ranging from structural racism to health efficacy, or confidence in one's ability to pursue a healthy life, and health literacy. 28,30 COVID-19 will stand as a particular flash point, as the ruptures of trust happen not just between the public and the government and healthcare institutions (eg, local hospitals, public health officials, 31,32 The ubiquity of this discord suggests that mixed adoption of COVID-19 mitigation strategies is reflective of other forms of social and bodily resistance related to political philosophy and stigma and blame. This observation builds on research emphasising the spatial dynamics of differentiation in this erosion of trust.…”
Section: Overlapping and Embedded Crisesmentioning
confidence: 99%
“…The pandemic has shown that there are not only material barriers to care, but also racial, ethnic, and political difficulties in the uptake of mitigation protocols, associated with factors ranging from structural racism to health efficacy, or confidence in one's ability to pursue a healthy life, and health literacy. 28 , 30 COVID-19 will stand as a particular flash point, as the ruptures of trust happen not just between the public and the government and health-care institutions (eg, local hospitals, public health officials, the US National Institutes of Health, and the Centers for Disease Control and Prevention) but, crucially, within communities, as neighbours engage in fractious debates on the nature of the COVID-19 threat in public spaces and online. 31 , 32 The ubiquity of this discord suggests that mixed adoption of COVID-19 mitigation strategies is reflective of other forms of social and bodily resistance related to political philosophy and stigma and blame.…”
Section: Overlapping and Embedded Crisesmentioning
confidence: 99%
“…( Table 2 ). Thirty-five studies mainly or totally used the term “food insecurity” [ 26 , 27 , 28 , 29 , 31 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ], six used “food security” [ 25 , 30 , 32 , 63 , 64 , 65 ], and five used both [ 66 , 67 , 68 , 69 , 70 ].…”
Section: Resultsmentioning
confidence: 99%